Plan de Marketing Estratégico para el Spa “Verónica Maldonado” en la ciudad de Catamayo periodo septiembre 2021 - febrero 2022 - Cueva Martínez, Ronald Fabricio (2022)
The Verónica Maldonado Spa has not been implemented a marketing plan until now, in which it can establish its objectives in commercial terms and develop strategies in order to achieve these goals, for this reason the current research has as general objective to develop a strategic marketing plan for the company under study, to contribute to the best development of its activities. For this, the internal and external diagnosis was elaborated, to determine the strengths, weaknesses, threats and opportunities, and based on this, propose adequate strategies. To achieve this objective, a descriptive research was used, which allowed to investigate the characteristics that affect the activities of the organization mentioned before, deductive and inductive methods were also used. As a starting point, the Political, Economic, Social and Technological (PEST) external analysis were carried out, then the evaluation of Porter's five forces was supported, with this it was possible to know that the company denotes a considerable response to the opportunities presented to it and the threats do not greatly affect to the company. To evaluate the competitiveness in the industry, the competitive profile matrix was developed, in which it was known that this company is on the podium, compared to its three direct competitors. In the internal analysis, the EFI matrix was implemented to know the strengths and weaknesses, where it was possible to appreciate that the organization is stronger than other ones. All the information collected from the different analyzes served for the development of the second objective, which is to make a marketing proposal, thanks to the information that was summarized in the SWOT matrix, the FO, DO, FA and DA strategies were determined and four strategic objectives were established, in response to the actual deficiencies in the entity, with its corresponding action plan, schedule and budget.